2013
DOI: 10.1128/aac.01576-12
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Does Not Prolong Corrected QT Intervals in Healthy Subjects

Abstract: We evaluated the effect of tigecycline (50-mg and 200-mg doses) on corrected QT (QTc) intervals and assessed safety and tolerability in a randomized, placebo-controlled, four-period crossover study of 48 (44 male) healthy volunteers aged 22 to 53 years. Fed subjects received tigecycline (50 mg or 200 mg) or placebo in a blinded fashion or an open-label oral dose of moxifloxacin (400 mg) after 1 liter of intravenous fluid. Serial electrocardiograms were recorded before, and for 96 h after, dosing. Blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…No adverse cardiovascular reactions are known for tigecycline. A study in healthy subjects showed that this compound has no significant effect on the QT interval [169].…”
Section: Nomentioning
confidence: 97%
“…No adverse cardiovascular reactions are known for tigecycline. A study in healthy subjects showed that this compound has no significant effect on the QT interval [169].…”
Section: Nomentioning
confidence: 97%